Quantitative probabalistic assessment of the risk of listeriosis from the consumption of milk from informal markets in Ghana - Appiah, J.; Tano-Debrah, K.; Annor, G.A.; Alpha, M.M.; Makita, K.; Grace, Delia (2011)
Background: Listeriosis is a group of disorders caused by the bacterium Listeria monocytogenes. The organism, which is considered to be recalcitrant to environmental stress such as freezing, refrigeration, drying and heating to a remarkable extent, is widely distributed in the environment and is consequently associated with various food products of both plant and animal origin including unpasteurized or under-pasteurized fresh cow’s milk. The disease has the highest case-fatality ratio of all food-borne diseases and it is considered as an emerging food-borne disease globally. In Ghana, the consumption of unpasteurized daily products is widely practiced in some milk producing communities. This study, aiming at improving the safety of animal-sourced foods, assessed the risk of consuming raw or unprocessed milk from the informal milk markets in Ghana that may be contaminated with Listeria monocytogenes and determined the best options for mitigating the problem. Methods: Modular Process Risk Models (MPRM) are a recent framework for quantitative microbial risk assessment. This identifies key steps and to each assigns one or more basic processes which can be described mathematically. A MPRM was developed to quantitatively assess the risk of consuming dairy products from the informal market contaminated with L. monocytogenes based on three risk inputs: the quantitative diary market chain model, information on handling of milk, and contamination rates of milk/milk products with L. monocytogenes in each pathway. Data from participatory rural appraisal and interviews of stakeholders of informal milk markets were used to model the quantitative diary market chains and milk handling practices. L. monocytogenes contamination rates were obtained by laboratory testing of milk samples from the chains. Results: L. monocytogenes was detected in samples from 42-47% of farms (production sites) and 79-84% of retail samples. The organism was detected in 21% of boiled milk samples and 52-84% in fermented milk samples. The MPRM identified up to ten steps between the farm and consumption and charcterised each according to the processes involved. The fermented milk samples were consumed in greater volumes than the boiled and untreated milk samples. Risk determination using Monte Carlo simulations and probability modeling suggested the risk of L. monocytogenes was highest with the fermented milk at the retail market, supporting the findings of the qualitative exposure assessment. Optimization of the boiling and fermentation processes could effectively reduce the risk of listeriosis. Summary: This proof of concept study used sophisticating modeling techniques along with information derived from participatory appraisals, showing how adapting tools to local contexts can generate useful evidence on food safety at a fraction of the cost of conventional risk assessment. The assessment was able to identify high risk products and consumer groups and hence lead to better risk management.